Analysis of the Effects of the Implementation of Cooperative Learning in Physical Education - Carlos Velázquez Callado (Qualitative Research in Education, 2012)
Our research was oriented to test the effects of a structured program of cooperative learning in Physical Education classes with students in grades 5 and 6 of primary school, with and without previous experience with this methodology. In a second phase we sought to determine how students perceived the received classes for a time later. We analysed data collected during implementation, through cooperative learning, of two teaching units to a total of six groups of students; in addition, a number of interviews, five individual and one collective, were carried out to a total of 10 former students who had left school between one and five years earlier. The results show the positive effects of cooperative learning on students' motor performance, and some social achievements such as a greater autonomy of the students in the learning process, an increasing in prosocial behaviours and the inclusion of pupils with special educational needs. On the other hand, as time went on, the students rated the received classes as cooperative, participatory, funny and useful, emphasizing peer support as a key factor that enabled them to learn in Physical Education.